Human CD1d–glycolipid tetramers generated by in vitro oxidative refolding chromatography - Karadimitris, Anastasios (The National Academy of Sciences, 2001)
CD1 molecules are specialized in presenting lipids to T lymphocytes, but identification and isolation of CD1-restricted lipidspecific T cells has been hampered by the lack of reliable and sensitive techniques. We here report the construction of CD1d–glycolipid tetramers from fully denatured human CD1d molecules by using the technique of oxidative refolding chromatography. We demonstrate that chaperone- and foldase-assisted refolding of denatured CD1d molecules and β(2)-microglobulin in the presence of synthetic lipids is a rapid method for the generation of functional and specific CD1d tetramers, which unlike previously published protocols ensures isolation of CD1d tetramers loaded with a single lipid species. The use of human CD1d–α-galactosylceramide tetramers for ex vivo staining of peripheral blood lymphocytes and intrahepatic T cells from patients with viral liver cirrhosis allowed for the first time simultaneous analysis of frequency and specificity of natural killer T cells in human clinical samples. Application of this protocol to other members of the CD1 family will provide powerful tools to investigate lipid-specific T cell immune responses in health and in disease.